Population mobility and adult orthopaedic trauma services during the COVID-19 pandemic: fragility fracture provision remains a priority. (2nd June 2020) - Scott, Chloe E. H.; Holland, George; Powell-Bowns, Matilda F. R.; Brennan, Caitlin M.; Gillespie, Matthew; Mackenzie, Samuel P.; Clement, Nick D.; Amin, Anish K.; White, Tim O.; Duckworth, Andrew D.
Abstract : Aims: This study aims to define the epidemiology of trauma presenting to a single centre providing all orthopaedic trauma care for a population of ∼ 900, 000 over the first 40 days of the COVID-19 pandemic compared to that presenting over the same period one year earlier. The secondary aim was to compare this with population mobility data obtained from Google. Methods: A cross-sectional study of consecutive adult (> 13 years) patients with musculoskeletal trauma referred as either in-patients or out-patients over a 40-day period beginning on 5 March 2020, the date of the first reported UK COVID-19 death, was performed. This time period encompassed social distancing measures. This group was compared to a group of patients referred over the same calendar period in 2019 and to publicly available mobility data from Google. Results: Orthopaedic trauma referrals reduced by 42% (1, 056 compared to 1, 820) during the study period, and by 58% (405 compared to 967) following national lockdown. Outpatient referrals reduced by 44%, and inpatient referrals by 36%, and the number of surgeries performed by 36%. The regional incidence of traumatic injury fell from 5.07 (95% confidence interval (CI) 4.79 to 5.35) to 2.94 (95% CI 2.52 to 3.32) per 100, 000 population per day. Significant reductions were seen in injuries related to sports and alcohol consumption. No admissions occurred relating to major trauma (Injury Severity Score > 16) or violence against the person. Changes in population mobility and trauma volume from baseline correlated significantly (Pearson's correlation 0.749, 95% CI 0.58 to 0.85, p < 0.001). However, admissions related to fragility fractures remained unchanged compared to the 2019 baseline. Conclusion: The profound changes in social behaviour and mobility during the early stages of the COVID-19 pandemic have directly correlated with a significant decrease in orthopaedic trauma referrals, but fragility fractures remained unaffected and provision for these patients should be maintained. Cite this article: Bone Joint Open 2020;1-6:182–189.